2021
DOI: 10.1111/1556-4029.14782
|View full text |Cite
|
Sign up to set email alerts
|

Forensic anthropology casework performance: Assessing accuracy and trends for biological profile estimates on a comprehensive sample of identified decedent cases

Abstract: The purpose of this study was to investigate the accuracy rates and trends in forensic anthropology casework concerning the estimation of the biological profile (sex, age, ancestry, and stature). Identified cases from the Forensic Anthropology Database for Assessing Methods Accuracy (FADAMA; n = 359) were analyzed to explore the following: accuracy rates per biological profile component, case-level performance in assessing the biological profile, and factors related to inaccuracy rates. Accuracy Highlights• Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Code §68.50.645, a primary role of the State Physical Anthropologist is to determine whether HSR are “Indian” or “Non‐Indian,” anachronistic terms that illustrate a key question for remains from both unmarked burials as well as forensic cases [34]. There is current debate among expert biological anthropologists and forensic anthropologists regarding the complications and validity of evaluating biological ancestry (or “race”) from HSR [35–38]. If experts with decades of experience disagree on the reliability of estimating ancestry or adult age or sex, etc., from HSR, how can anyone with less experience and education provide meaningful information?…”
Section: Discussionmentioning
confidence: 99%
“…Code §68.50.645, a primary role of the State Physical Anthropologist is to determine whether HSR are “Indian” or “Non‐Indian,” anachronistic terms that illustrate a key question for remains from both unmarked burials as well as forensic cases [34]. There is current debate among expert biological anthropologists and forensic anthropologists regarding the complications and validity of evaluating biological ancestry (or “race”) from HSR [35–38]. If experts with decades of experience disagree on the reliability of estimating ancestry or adult age or sex, etc., from HSR, how can anyone with less experience and education provide meaningful information?…”
Section: Discussionmentioning
confidence: 99%
“…Skull and bone form are reliable characteristics, but craniometrics can provide real advantages as the most objective means of generating data. 4 Statistical analysis of the skull is best achieved using reliable, well-established osteometric methods. 5 , 6 In recent years, craniometric measurements have become an important tool used by anthropologists, forensic experts and reconstructive surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Many academic papers exist discussing research into postcranial skeletons in different populations. 4 , 7 , 8 , 9 Forensic processes in many countries apply the craniometric techniques based on the skull measurements of individuals of known gender and race developed by Е. Giles. 1 , 9 , 10 Throughout the CIS (Commonwealth of Independent States), including the Republic of Kazakhstan, independently of the population living here, forensic experts use conditionally accepted craniometric criteria developed by V.I.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tracking decedent race and ethnicity allows researchers to provide insight into decedent trends. Recent studies have provided forensic anthropology with a clearer sense of the demographics of decedents common in forensic anthropology cases where the decedents were successfully identified [ 22 , 23 ]. Notably, research indicated that Black and Hispanic persons were disproportionately overrepresented in forensic anthropology casework when compared to U.S. census data population proportions.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, this approach considers how categories and terms used to describe the reference samples represent social meaning relevant to local communities [ 17 , 30 , 31 ]. Several studies propose that current methodological approaches and reference sample representation may be impacting the accuracy rates of ancestry estimation, and suggest that increasing diversity of reference samples would better serve the forensic anthropological casework demographics [ 22 , 23 ]. Furthermore, Go and colleagues [ 33 ] documented how those conducting ancestry-related research, as well as the skeletal samples used, are largely WEIRD (Western, educated, industrialized, rich, and democratic).…”
Section: Introductionmentioning
confidence: 99%